2015
DOI: 10.1007/s10854-015-2794-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of La modified Bi5Ti3FeO15 ceramics

Abstract: The polycrystalline samples of a new bismuth Bi-ferrite, Bi 4 LaTi 3 FeO 15 (i.e., combination of multiferroic BiFeO 3 and ferroelectric Bi 4 Ti 3 O 12 in equal molar ratios) of Aurivillius structural family, were prepared using a hightemperature solid-state reaction method (calcinations/sintering temperature = 900-1,100°C). The X-ray diffraction studies have confirmed the formation of single-phase compounds in orthorhombic crystal system. The scanning electron microscope has provided uniform-grained microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This behavior is due to the different types of polarization (i.e. dipolar, ionic, electronic, and interfacial) and the accumulation of charge carriers on the surface and at grain boundaries, known as the Maxwell-Wagner effect 5,19 . Therefore, we focus on the dielectric properties of samples at higher frequencies since it properly exhibits the intrinsic polarizability of samples.…”
Section: The Refined Lattice Parameters and Cell Volume Of Single-phamentioning
confidence: 99%
“…This behavior is due to the different types of polarization (i.e. dipolar, ionic, electronic, and interfacial) and the accumulation of charge carriers on the surface and at grain boundaries, known as the Maxwell-Wagner effect 5,19 . Therefore, we focus on the dielectric properties of samples at higher frequencies since it properly exhibits the intrinsic polarizability of samples.…”
Section: The Refined Lattice Parameters and Cell Volume Of Single-phamentioning
confidence: 99%
“…Figure 12 shows frequency variation of conductance (Y 0 ) for all prepared CTFO nanoperovskites at different temperatures. These are denoted as individual admittance of cumulative microstructure model with the help of series resistive and capacitive components, known as bricklayer model [61]. It is clearly observed that the space charges are to be released from the surface electrodes at higher frequencies.…”
Section: Complex Impedance Spectroscopy Analysismentioning
confidence: 99%
“…In view of the above, structural, dielectric, electrical and magnetic properties of a new multioferroic fabricated with ferroelectric Bi 4 Ti 3 O 12 (T c = 650°C) and BiFeO 3 in equal molecular ratio (i.e., Bi 5 Ti 3 FeO 15 ) have been reported [16][17][18][19][20][21][22][23][24]. Because of multiple advantages of addition of lanthanum in ferroelectrics or/and multiferroics, we have recently carried out extensive studies of structural, dielectrics and ferroelectric properties of La modified ferroelectric/multiferroics Bi 5 Ti 3 FeO 15 , and reported some of them [25,26]. In the present paper, we report the structural, dielectric, impedance, electric modulus and transport properties of Bi 3 La 2 Ti 3 FeO 15 (BLTFO).…”
Section: Introductionmentioning
confidence: 99%